J-aggregation, its impact on excited state dynamics and unique solvent effects on macroscopic assembly of a core-substituted naphthalenediimide1. Issue 15 (21st April 2015) - Kar, Haridas; Gehrig, Dominik W.; Laquai, Frédéric; Ghosh, Suhrit
<x xml:space="preserve">Abstract</x> H-bonding promoted J-aggregation of an amine-substituted NDI significantly stabilizes the charge-separated state and exhibits contrasting morphologies depending on solvent structure.